An economic analysis of rubber production in Malaysia using ARDL model / Muhammad Burhanuddin Ismail - Ismail, Muhammad Burhanuddin (Faculty of Plantation and Agrotechnology, 2018)
Rubber industry is one of the main contributors to Malaysia’s economic growth. But, lately Malaysia facing a declining in area and production of rubber. The study determines the economic analysis of rubber production in Malaysia using annual data over the period of 1987-2016. The importance of this study comes from the necessity to determine important factors influencing of rubber production in Malaysia. An Autoregressive Distributed Lag (ARDL) modelling is employed to investigate the impact of area planted, rubber export, and synthetic rubber price on rubber production. The findings of the study illustrate that the ADF unit root tests indicate that the independent variable at first difference are stationary. The results of estimated long run coefficients using the ARDL Approach for the Rubber Export and Area planted are positively significant. The cumulative sum of recursive residuals (CUSUM) were used to test for structural stability of the model. The ARDL bounds tests suggest that the independent variable series are co-integrated. The ECM also reveals that the independent variable have significant causative implications for rubber production and able to readjust 56.12% to long-run equilibrium.